2000
DOI: 10.1103/physrevlett.84.701
|View full text |Cite
|
Sign up to set email alerts
|

Novel SiGe Island Coarsening Kinetics: Ostwald Ripening and Elastic Interactions

Abstract: Real-time light scattering measurements of coherent island coarsening during SiGe/Si heteroepitaxy reveal unusual kinetics. In particular, the mean island volume increases superlinearly with time, while the areal density of islands decreases at a faster-than-linear rate. Neither observation is consistent with standard considerations of Ostwald ripening. Modification of the standard theory to incorporate the effect of elastic interactions in the growing island array reproduces the observed behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
80
0
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 22 publications
7
80
0
4
Order By: Relevance
“…When the film is infinitely thick or when the substrate is infinitely rigid, different theoretical [14,15] and numerical [16,17,18,19] approaches revealed finite-time singularities enforced by elastic stress concentration which account for experiments in thick films [8,9] where dislocations can finally develop. However, these models can not describe experiments of thin films in the Stranski-Krastanov type of growth [5,6] where the surface organizes smoothly into islands separated by a wetting layer and evolving with a coarsening dynamics under annealing [6]. A crucial issue for these systems is the wetting of the substrate by the film [20,21] which is a good candidate for regularizing the dynamics of the instability.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…When the film is infinitely thick or when the substrate is infinitely rigid, different theoretical [14,15] and numerical [16,17,18,19] approaches revealed finite-time singularities enforced by elastic stress concentration which account for experiments in thick films [8,9] where dislocations can finally develop. However, these models can not describe experiments of thin films in the Stranski-Krastanov type of growth [5,6] where the surface organizes smoothly into islands separated by a wetting layer and evolving with a coarsening dynamics under annealing [6]. A crucial issue for these systems is the wetting of the substrate by the film [20,21] which is a good candidate for regularizing the dynamics of the instability.…”
mentioning
confidence: 99%
“…for quantum dots, wires and electronic devices with specific confinement properties [4]. A notorious experimental example is Si/Ge films on a Si substrate which exhibit a variety of structures such as pre-pyramids, pyramids, domes and huts [5,6]. Such epitaxial films experience an elastic stress due to the misfit with the substrate which is relaxed by a morphological instability similar to the Asaro-Tiller-Grinfeld thermodynamical instability in solid-liquid interfaces [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An array of hut clusters selforders on a square mesh with increasing areal coverage. In case of a dense array of islands, Floro et al [61] found that ordering occurs to minimize the repulsive elastic interactions between neighbouring islands. However, self-organization breaks down when islands coalesce during deposition or static coarsening.…”
Section: Dense Arrays Of Islandsmentioning
confidence: 99%